THE USE OF PRODUCTIVITY GAIN SHARING MODEL IN INCREASING PRODUCTIVITY OF MSMEs HERBAL PRODUCTS DURING THE COVID-19 PANDEMIC ERA TO ACHIEVE SUSTAINABLE DEVELOPMENT GOALS (SDGs) IN INDONESIA - Dyah Lintang Trenggonowati; Kulsum Kulsum; Asep Ridwan; Sirajuddin Sirajuddin (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
During the COVID-19 pandemic, industrial product exports rose by 41%, driven by herbal products. Micro, small, and medium-sized enterprises (MSMEs) significantly contribute to the growth in export value. The growth is consistent with the primary objective of MSMEs, which is to promote economic, social, and environmental development. Exports rose due to improved production, which aided in the sustainability of MSMEs producing herbal goods. Increased MSME production results in increased community welfare, an objective of the Sustainable Development Goals (SDGs). However, there is a shortage of research on how to improve the productivity of MSMEs substantially. There is no reference for MSMEs to use the productivity profit-sharing model to monitor, forecast, and assess their productivity level. This research will undertake a more detailed examination of productivity benefit-sharing, examining the role and contribution of productivity to the sustainability of MSMEs in Indonesia's pursuit of the SDGs. The approach used in this research is quantitative. Increased productivity is associated with an increase in total factor productivity (TFP). TFP seeks to deliver products effectively and efficiently via the use of the output-to-input ratio. By and large, productivity gains sharing for MSME herbal goods boosted added value (NT) by 500 percent between 2019 and 2020, or fivefold between 2018 and 2019.